On the matter of European indicator of language competence and a framework strategy for multilingualism - Isayeva, O.V. (Культура народов Причерноморья, 2013)
The article describes the mechanism for determining the European indicator of language competence. The concept of "language competence" is used to define the terminology of linguistic units required for successful communication. The Council of Europe confirmed the need to implement measures to obtain reliable and comparable data on the results of training and learning foreign languages in the EU member states and defined the main requirements for them: the objective test that provides the reliability, accuracy and validity of the results, the ability to identify innovative approaches and sharing of best practices in education policy. Key words: language competence, proficiency level, assessment, linguistic skills, multilingualism.